2008
DOI: 10.2500/aap.2008.29.3121
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline treatment results in reduced oral steroid requirements in adult asthma

Abstract: The tetracycline antibiotics have pleiotropic anti-inflammatory properties that may explain their therapeutic benefit in rheumatoid arthritis and acne. As these agents suppress both cellular and humoral immune responses, they may be of benefit in treating asthma and other allergic disorders. The purpose of this study was to determine whether minocycline therapy of asthma has steroid sparing effects beyond its inherent antibiotic properties. Adult asthmatic patients (n = 17) were treated with minocycline 150 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Because of its lipophilicity, minocycline has significant tissue penetration and accumulates in leukocytes, suggesting even higher concentrations in these areas and cells. Most importantly, minocycline treatment was found to be effective in clinical trials for multiple sclerosis, rheumatoid arthritis, and asthma, in which beneficial effects have been linked to minocycline's capacity as an immunomodulatory agent for T cells [28][29][30]. These observations, and other findings by our group, strongly suggest that the therapeutic effects of minocycline we observed in vitro should be achievable in vivo [7].…”
Section: Discussionsupporting
confidence: 68%
“…Because of its lipophilicity, minocycline has significant tissue penetration and accumulates in leukocytes, suggesting even higher concentrations in these areas and cells. Most importantly, minocycline treatment was found to be effective in clinical trials for multiple sclerosis, rheumatoid arthritis, and asthma, in which beneficial effects have been linked to minocycline's capacity as an immunomodulatory agent for T cells [28][29][30]. These observations, and other findings by our group, strongly suggest that the therapeutic effects of minocycline we observed in vitro should be achievable in vivo [7].…”
Section: Discussionsupporting
confidence: 68%
“…Finally, these minocycline-mediated decreases in IgE responses were associated with the suppression of p38 MAPK in the T lymphocytes of these patients (Joks and Durkin, 2011a,b). These effects may account for the improvement observed in allergic asthmatic patients after minocycline treatment in a randomized, double-blind, placebo-controlled, crossover study (Daoud et al, 2008). In that trial, the patients' asthma symptoms and spirometric outcomes were significantly improved, and their oral steroid requirements reduced, findings that indicate the potential usefulness of minocycline for treating asthma.…”
Section: Effects Of Minocycline On Allergic Asthmamentioning
confidence: 64%
“…Joks and Durkin (reviewed in Ref. 8), in a pioneering study, showed that minocycline harbors oral steroid-sparing properties in a cohort of human subjects with both moderate persistent and severe persistent asthma (5). Minocycline was shown to be efficacious in reducing IgE production in an in vitro system as well as in response to BPO(14)-KLH (6,42).…”
Section: Discussionmentioning
confidence: 99%